Highly Reproducible Surface-Enhanced Raman Scattering Detection of Alternariol Using Silver-Embedded Silica Nanoparticles - Hahm, Eunil (Sensors (Basel), 2020)
Alternariol (AOH) is a mycotoxin from fungi that has been found in processed foods due to its high thermal stability. To address the complexity and costs of conventional AOH detection methods, we propose an alternative based on surface-enhanced Raman scattering (SERS) and specially designed nanoparticle substrate. Herein, silver-embedded silica (SiO(2)@Ag) nanoparticles with a highly reproducible SERS signal were successfully developed for detecting AOH. Silica nanoparticles (~145 nm) were used as a template to deposit silver nanoparticles (~17 nm), thereby generating SiO(2)@Ag. The SiO(2)@Ag nanoparticles showed a good linearity between SERS signal intensity and AOH concentrations from 16 to 1000 nM with a limit of detection of 4.83 nM. Additionally, the SERS signal of the SiO(2)@Ag nanoparticles was highly reproducible, with relative standard deviations of 2.33–5.95% in the AOH concentration range from 10 to 10,000 nM, demonstrating the reliability of the proposed SERS method.